Inhibition of ERK signaling potentiates the anti-tumor activity of FL118 on hepatocellular carcinoma cells - Ma, Qingxia; Wang, Dong; Zhang, Heng; Yang, Zhihong; Yang, Yuecheng; Ji, Lixia; Liu, Zhantao; Zhao, Hongqin; Jiang, Guohui (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: A novel camptothecin analogue, FL118, has been shown to exhibit superior anticancer activity over irinotecan on colon and lung cancer cells. It was reported that FL118 mainly performs its broadspectrum anticancer activity through inducing cancer cell apoptosis. Accumulated evidence indicated that ERK pathway was constitutively activated in liver cancer, thereby promoting tumorigenesis, development, metastasis and recurrence. In this study, we aimed to investigate the anticancer potency of FL118 on liver cancer cell lines and the effect of FL118 on extracellular regulated protein kinase (ERK) pathway. Methods: Viability of PLC and Huh7 cells was detected by MTT assay. Western blot assay was performed to assess phosphorylated and total ERK protein. And cell apoptosis was measured by Hochest-PI staining. Results: Our results revealed that FL118 can inhibit PLC and Huh7 cell viability and markedly induce their apoptosis. Western blot results indicated that ERK pathway was activated in huh7 and PLC cells after administration of FL118. In addition, the pro-apoptotic and antiviability ability of FL118 can be potentiated by ERK-specific inhibitor U0126. Conclusions: Our study confirmed good anticancer activity of FL118 on liver cancer, and targeting ERK pathway can significantly improve its anticancer potency.